PENGARUH KEAKTIFAN BERORGANISASI, DUKUNGAN KELUARGA, DAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK MAHASISWA FKIP UNS - Sajida Salwa Sholikah; Mintasih Indriayu (FKIP Unswagati, 2025)
This study aims to determine the influence of organizational involvement, family support, and learning motivation on the academic achievement of FKIP UNS students. This research is a descriptive study with a quantitative approach. The population consisted of students who participated in the Study Program Student Association (HMP) at FKIP in the 2025 period, with a total sample of 151 students selected using proportional random sampling. Data was collected using a questionnaire with a four-point Likert scale. The data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics 25. The results showed that organizational involvement, family support, and learning motivation together had a positive and significant effect on academic achievement, with an F-value of 95.807 > F-table of 2.666 and a significance value of 0.000 < 0.050. This study shows that the higher the students’ organizational involvement, the greater the family support they receive, and the stronger their learning motivation, the more their academic achievement will improve. Keywords: organizational activities, family support, learning motivation, academic achievement